Demokratins Bilder : Fotografi och bildkonst efter apartheid. - Bester, Rory; Enwezor, Okwui; Godby, Michael; Lundström, Jan-Erik; Mofokeng, Santu; Pierre, Katarina; Uppsala Konstmuseum, Uppsala; Boras Konstmuseum, Boras (Umea : BildMuseet, 1998)
Bieber, Jodi ; Brundrit, Jean ; Hassan, Kay ; Marasela, Senzeni ; Mofokeng, Santu ; Motau, Ruth ; Mtethwa, Zwelethu ; Nunn, Cedric ; Rose, Tracey ; Schonfeldt, Joachim ; Siopsis, Penny ; Vari, Minnette
biografie
Demokratins Bilder : Fotografi och bildkonst efter apartheid, BildMuseet, Umea, 6.9. - 8.11.1998 ; Uppsala Konstmuseum, Uppsala, 14.11.1998 - 17.1.1999 ; Boras Konstmuseum, Boras, 13.3 - 25.4.1999
Engels & Zweeds
kunstcatalogus